2015
DOI: 10.3109/02813432.2015.1067513
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions in a primary care population prescribed non-steroidal anti-inflammatory drugs

Abstract: Objective. To determine how often patients with musculoskeletal (MSK) complaints prescribed a non-steroidal anti-inflammatory drug (NSAID) subsequently consult their general practitioner (GP) with a non-serious adverse drug reaction (ADR). Design. Cohort study. Setting. A healthcare database containing the electronic GP medical records of over 1.5 million patients throughout the Netherlands. Patients. A total of 16 626 adult patients with MSK complaints prescribed an NSAID. Main outcome measures. The patients’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
4
0
2
Order By: Relevance
“…10,12 We found NSAID side effect reactions, including some potentially mild (i.e., gastrointestinal complaints, dizziness, headache) and some potentially severe (e.g., nephrotoxicity) that are similar to prior data. 1,12,25 Patients prescribed only COX-2 inhibitors had a lower overall one-year ADR incidence using the standard definition (1.3%), although using the expanded definition, incidence was similar (1.9%). For these patients, HSRs comprised a greater proportion of the ADRs (28.2% using the standard definition and 26.5% using the expanded definition).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…10,12 We found NSAID side effect reactions, including some potentially mild (i.e., gastrointestinal complaints, dizziness, headache) and some potentially severe (e.g., nephrotoxicity) that are similar to prior data. 1,12,25 Patients prescribed only COX-2 inhibitors had a lower overall one-year ADR incidence using the standard definition (1.3%), although using the expanded definition, incidence was similar (1.9%). For these patients, HSRs comprised a greater proportion of the ADRs (28.2% using the standard definition and 26.5% using the expanded definition).…”
Section: Discussionsupporting
confidence: 83%
“…10,12 However, these studies have included all “allergies” -- inclusive of both HSRs and side effects -- in their frequency estimates. Additionally, although electronic health records (EHRs) contain both coded and non-coded (i.e., free-text) data, prior incidence estimates of NSAID allergy from EHR data used only coded elements, which may have underestimated HSR burden.…”
Section: Introductionmentioning
confidence: 99%
“…This finding may have safety implications as it was suggested that among patients seeking NSAIDs following musculoskeletal complaints, 6% incur in adverse events. 27 …”
Section: Discussionmentioning
confidence: 99%
“…In the primary care setting, Koffeeman et al conducted a retrospective cohort study using a database of 1.5 million patients in the Netherlands who were prescribed NSAIDs due to musculoskeletal pain symptoms [ 66 ]. They found that 6% of all patients consulted their primary care provider due to non-serious potential adverse drug reactions and the most common symptom was dyspepsia (32%).…”
Section: Drug Interactionmentioning
confidence: 99%